Whole‐brain intracranial vessel wall imaging at 3 Tesla using cerebrospinal fluid–attenuated T1‐weighted 3D turbo spin echo - Zhaoyang Fan; Qi Yang; Zixin Deng; Yuxia Li; Xiaoming Bi; Shlee Song; Debiao Li (2016)
Purpose Although three‐dimensional (3D) turbo spin echo (TSE) with variable flip angles has proven to be useful for intracranial vessel wall imaging, it is associated with inadequate suppression of cerebrospinal fluid (CSF) signals and limited spatial coverage at 3 Tesla (T). This work aimed to modify the sequence and develop a protocol to achieve whole‐brain, CSF‐attenuated T 1 ‐weighted vessel wall imaging. Methods Nonselective excitation and a flip‐down radiofrequency pulse module were incorporated into a commercial 3D TSE sequence. A protocol based on the sequence was designed to achieve T 1 ‐weighted vessel wall imaging with whole‐brain spatial coverage, enhanced CSF‐signal suppression, and isotropic 0.5‐mm resolution. Human volunteer and pilot patient studies were performed to qualitatively and quantitatively demonstrate the advantages of the sequence. Results Compared with the original sequence, the modified sequence significantly improved the T 1 ‐weighted image contrast score (2.07 ± 0.19 versus 3.00 ± 0.00, P = 0.011), vessel wall‐to‐CSF contrast ratio (0.14 ± 0.16 versus 0.52 ± 0.30, P = 0.007) and contrast‐to‐noise ratio (1.69 ± 2.18 versus 4.26 ± 2.30, P = 0.022). Significant improvement in vessel wall outer boundary sharpness was observed in several major arterial segments. Conclusions The new 3D TSE sequence allows for high‐quality T 1 ‐weighted intracranial vessel wall imaging at 3 T. It may potentially aid in depicting small arteries and revealing T 1 ‐mediated high‐signal wall abnormalities. Magn Reson Med 77:1142–1150, 2017. © 2016 International Society for Magnetic Resonance in Medicine